A New Approach for Classifying Chilean Universities - Reyes, Claudia; Rosso, Pedro (International Higher Education, 2012)
Using a new approach, Chilean universities were classified in four categories that showed marked differences in several indicators, including academic performance. This type of classification could be applicable in other countries.